2010
DOI: 10.1105/tpc.109.068296
|View full text |Cite
|
Sign up to set email alerts
|

MGOUN1Encodes anArabidopsisType IB DNA Topoisomerase Required in Stem Cell Regulation and to Maintain Developmentally Regulated Gene Silencing

Abstract: Maintenance of stem cells in the Arabidopsis thaliana shoot meristem is regulated by signals from the underlying cells of the organizing center, provided through the transcription factor WUSCHEL (WUS). Here, we report the isolation of several independent mutants of MGOUN1 (MGO1) as genetic suppressors of ectopic WUS activity and enhancers of stem cell defects in hypomorphic wus alleles. mgo1 mutants have previously been reported to result in a delayed progression of meristem cells into differentiating organ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 56 publications
6
69
0
Order By: Relevance
“…For example, strong alleles of the mutant of DNA polymerase « showed a sporophytic embryo-defective phenotype (Jenik et al, 2005;Ronceret et al, 2005), while fasciated stems were only found occasionally in the weak alleles (Yin et al, 2009). Similarly, disruption of DNA topoisomerase 1a in combination with reduction of DNA topoisomerase 1b caused seedling lethality, while disruption of DNA topoisomerase 1a alone only caused fasciation Graf et al, 2010). Thus, the phenotype of a mutant may largely depend on the severity and type of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, strong alleles of the mutant of DNA polymerase « showed a sporophytic embryo-defective phenotype (Jenik et al, 2005;Ronceret et al, 2005), while fasciated stems were only found occasionally in the weak alleles (Yin et al, 2009). Similarly, disruption of DNA topoisomerase 1a in combination with reduction of DNA topoisomerase 1b caused seedling lethality, while disruption of DNA topoisomerase 1a alone only caused fasciation Graf et al, 2010). Thus, the phenotype of a mutant may largely depend on the severity and type of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fasciated mutants with defects in BRU1/MGO3/TSK, which is thought to be involved in chromatid separation during mitosis (Takeda et al, 2004;Suzuki et al, 2005), are hypersensitive to DNA damage agents, show a release of gene silencing, and are delayed in cell cycle progression. Furthermore, MGO1, which encodes a type-IB DNA topoisomerase, was shown to be involved in stem cell regulation Graf et al, 2010). DNA polymerase « was shown to influence the cell cycle, embryo patterning, epigenetic regulation, somatic homologous recombination, and ABA signaling (Jenik et al, 2005;Yin et al, 2009).…”
mentioning
confidence: 99%
“…All transgenic lines were generated in the Landsberg erecta background. wus-7, wus-1, and clv3-2 have been described previously (4,8,34). Preparation for live imaging, Dex treatment, the optics, the microscopy platform (Zeiss 510 LSM), image acquisition, and image reconstruction have been described in earlier studies (6,13,33).…”
Section: Methodsmentioning
confidence: 99%
“…during inflorescence meristem growth is less sensitive (Graf et al, 2010). Furthermore, both WUS and WOX5 are essential in regenerating stem cells via tissue culture (Su et al, 2009;Sugimoto et al, 2010).…”
Section: Comparison With Arabidopsismentioning
confidence: 99%